Cyber‐Physical Watermarking with Inkjet Edible Bioprinting. (27th January 2022) - Jeon, Hee‐Jae; Leem, Jung Woo; Ji, Yuhyun; Park, Sang Mok; Park, Jongwoo; Kim, Kee‐Young; Kim, Seong‐Wan; Kim, Young L.
Abstract: Counterfeit medicines are a fundamental healthcare problem, threatening patient safety and public health as well as causing economic damage. Online pharmacies and the ongoing pandemic have promoted medicine counterfeiting. However, the existing anticounterfeit methods are limited because of material toxicity, low security, and complicated fabrication. Here a dosage‐level security method is introduced that combines digital watermarking and physical printing at the material level. A set of requirements is designed to ensure the edibility, printability, imperceptibility, and robustness of cyber‐physical watermarking. An inkjet printer using safe food coloring is adapted to print a watermarked image on a recombinant luminescent silk protein taggant to enhance attack resistance. Machine learning of color accuracy recovers unavoidable color distortions during printing and acquisition, allowing robust smartphone readability. An edible watermarked taggant affixed to each individual medicine can offer anticounterfeit and authentication features at the dosage level, empowering every patient to aid in abating illicit medicines. Abstract : A cyber‐physical security platform by combining digital watermarking and edible printing is devised for serialization, track and trace, and authentication at dosage levels, not at the packaging level. The digital and material properties are hybridized into edible watermarking without material toxicity or cytotoxicity for medicines. The reported method can allow patients to play a major role in combating anticounterfeit medicines.